1988
DOI: 10.1007/bf00144746
|View full text |Cite
|
Sign up to set email alerts
|

Risk of HIV infection on patients and staff of two dialysis centers: Seroepidemiological findings and prevention trends

Abstract: In view of the present world-wide diffusion of HIV, we evaluated the possible presence of persons infected by HIV or suffering from AIDS among the patients and staff of two Dialysis Centers. In the past these centers have been found to be at a high risk for HBV infection. The results of this seroepidemiological study, though rather reassuring for the time being, have led the authors to propose specific prevention rules, owing to the nature of activities in these medical structures and in light of the fact that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Of the 3,420 participants, two surgeons, both of whom reported nonoccupational risk factors, were HIV positive (258). Other seroprevalence studies similarly have shown low rates of HIV seropositivity among HCWs without nonoccupational risk factors for HIV infection (Table 6) (20,66,71,80,82,107,117,118,123,163,215,264 One limitation of seroprevalence studies is that the extent of occupational and nonoccupational exposure to HIV among tested workers is usually unknown. Also, the rates may be underestimates if individuals deferred testing because they knew they were or suspected they might be HIV positive.…”
Section: Hiv Seroprevalence Surveys Among Hcwsmentioning
confidence: 99%
“…Of the 3,420 participants, two surgeons, both of whom reported nonoccupational risk factors, were HIV positive (258). Other seroprevalence studies similarly have shown low rates of HIV seropositivity among HCWs without nonoccupational risk factors for HIV infection (Table 6) (20,66,71,80,82,107,117,118,123,163,215,264 One limitation of seroprevalence studies is that the extent of occupational and nonoccupational exposure to HIV among tested workers is usually unknown. Also, the rates may be underestimates if individuals deferred testing because they knew they were or suspected they might be HIV positive.…”
Section: Hiv Seroprevalence Surveys Among Hcwsmentioning
confidence: 99%
“…HIV does not spontaneously penetrate intact skin, and airborne transmission of these viruses does not occur [11][12][13]. Other seroprevalence studies similarly have shown low rates of HIV seropositivity among HCWs without non-occupational risk factors for HIV infection [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…6 Additional seroprevalence studies in HCWs, including surgeons, dentists, and even morticians, have consistently documented a very low positive rate when those with risk factors other than occupational exposure were excluded ( Table 1). 7–17 Although these analyses do not quantify the extent of exposure to HIV precisely in most of the workers tested, they are useful in that they do not suggest a high rate of previously unidentified infection among those groups studied.…”
Section: Seroprevalent Studies In Healthcare Workersmentioning
confidence: 99%